USEFUL METHODS FOR TEACHING READING AND SPEAKING TO SECONDARY SCHOOL LEARNERS - Abdujalilova, Shakhnoza (International Conference on Science, Education & Law, 2025)
Currently, in connection with the formation of an intercultural society, the need to develop unprepared speech skills among high school students is increasing. Many works of psychologists and methodologists are devoted to the problems of formation of speech skills. This scientific useful methods of teaching reading and speech to high school students in the article see we go out.